2012
DOI: 10.1186/1471-2199-13-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of microRNA-34a by NF-kappa B in human esophageal cancer cells

Abstract: BackgroundmiR-34a functions as an important tumor suppressor during the process of carcinogenesis. However, the mechanism of miR-34a dysregulation in human malignancies has not been well elucidated. Our study aimed to further investigate the regulation mechanism of miR-34a.ResultsWe found that overexpression of NF-kappa B p65 subunit could increase miR-34a levels in EC109, an esophageal squamous cancer cell line, while ectopic expression of DN IkappaB leaded to a significant reduction of miR-34a expression. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 37 publications
5
95
0
Order By: Relevance
“…MiR‐34a is a known tumour suppressor and key regulator miRNA in HNSCC,17, 23 and our prior in vivo findings showed that acidic bile down‐regulated miR‐34a levels in treated laryngopharyngeal mucosa. Although previous studies reported NF‐κB binding sites on the promoter of miR‐34a,21, 56 and an increase in miR‐34a levels in oesophageal cells under NF‐κB activation,21 the exact mechanism of miR‐34a regulation by NF‐κB is not yet obvious. Alternatively, it has been shown that STAT3 can directly repress miR‐34a, while an active IL‐6R/STAT3/miR‐34a loop was found necessary for EMT, invasion and metastasis of colorectal cancer cell line 56.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…MiR‐34a is a known tumour suppressor and key regulator miRNA in HNSCC,17, 23 and our prior in vivo findings showed that acidic bile down‐regulated miR‐34a levels in treated laryngopharyngeal mucosa. Although previous studies reported NF‐κB binding sites on the promoter of miR‐34a,21, 56 and an increase in miR‐34a levels in oesophageal cells under NF‐κB activation,21 the exact mechanism of miR‐34a regulation by NF‐κB is not yet obvious. Alternatively, it has been shown that STAT3 can directly repress miR‐34a, while an active IL‐6R/STAT3/miR‐34a loop was found necessary for EMT, invasion and metastasis of colorectal cancer cell line 56.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have demonstrated that deregulation of “oncomirs” miR‐21, miR‐155, miR‐192 and tumour suppressor miR‐375, miR‐451a and miR‐34a is associated with laryngopharyngeal cancer 12, 13, 14, 15, 16, 17. Moreover, an independent association has been demonstrated between NF‐κB activation and up‐regulation of oncogenic miR‐21 and/or down‐regulation of tumour suppressor miR‐34a and miR‐451a 21, 22, 23…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, there was also evidence indicating that NF-κB inhibited SIRT1 expression and signaling. Reportedly, NF-κB could increase the expression of microRNA-34a (miR-34a), which targeted the 3′UTR of SIRT1 and inhibited SIRT1 expression (138)(139)(140)(141). SIRT1 even became cleaved in inflammatory status (78,79).…”
Section: Regulation By Transcription Factorsmentioning
confidence: 99%
“…(20) The NF-κB transduction pathway is constitutively activated in human esophageal cell lines, suggesting that some of the proteins involved in the pathway play critical roles in carcinogenesis of the esophagus. (21,22) Our experiment showed that in Eca190 cells, TLD inhibited the expression of several proteins in the NF-κB signal pathway, including IKKβ, NF-κB, TNF-α and IL-1β, which is probably the pharmacological mechanism of the regulation of cell proliferation.…”
Section: Expression Of Proteins In the Signal Pathway Mediated By Nf-κbmentioning
confidence: 96%